HOME2 Study: Household Versus Personalized Decolonization in Households of Children With Methicillin-Resistant Staphylococcus aureus Skin and Soft Tissue Infection—A Randomized Clinical Trial. (10th June 2020) - Hogan, Patrick G; Parrish, Katelyn L; Mork, Ryan L; Boyle, Mary G; Muenks, Carol E; Thompson, Ryley M; Morelli, John J; Sullivan, Melanie L; Hunstad, David A; Bubeck Wardenburg, Juliane; Rzhetsky, Andrey; Gehlert, Sarah J; et al.
Abstract: Background: A household approach to decolonization decreases skin and soft tissue infection (SSTI) incidence, though this is burdensome and costly. As prior SSTI increases risk for SSTI, we hypothesized that the effectiveness of decolonization measures to prevent SSTI when targeted to household members with prior year SSTI would be noninferior to decolonizing all household members. Methods: Upon completion of our 12-month observational Household Observation of Methicillin-resistant Staphylococcus aureus in the Environment (HOME) study, 102 households were enrolled in HOME2, a 12-month, randomized noninferiority trial. Pediatric index patients with community-associated methicillin-resistant Staphylococcus aureus (MRSA) SSTI, their household contacts, and pets were enrolled. Households were randomized 1:1 to the personalized (decolonization performed only by household members who experienced SSTI during the HOME study) or household (decolonization performed by all household members) approaches. The 5-day regimen included hygiene education, twice-daily intranasal mupirocin, and daily bleach-water baths. At 5 follow-up visits in participants' homes, swabs to detect S. aureus were collected from participants, environmental surfaces, and pets; incident SSTIs were ascertained. Results: Noninferiority of the personalized approach was established for the primary outcome 3-month cumulative SSTI: 23 of 212 (10.8%) participants reported SSTI in household approach households, while 23 of 236 (9.7%) participants reported SSTI in personalized approach households (difference in proportions, −1.1% [95% confidence interval, −6.7% to 4.5%]). In multivariable analyses, prior year SSTI and baseline MRSA colonization were associated with cumulative SSTI. Conclusions: The personalized approach was noninferior to the household approach in preventing SSTI. Future studies should interrogate longer durations of decolonization and/or decontamination of the household environment to reduce household MRSA burden. Clinical Trials Registration: NCT01814371. Abstract : In households affected by methicillin-resistant Staphylococcus aureus, a decolonization regimen targeted to household members with a history of skin and soft tissue infection (SSTI) in the prior year was noninferior in preventing SSTI vs decolonization of all household members.